ASSOCIATION OF BACTERIAL AND VIRAL AGENTS IN ACUTE PNEUMONIA IN YOUNG ALPACAS - Guzmán M., Karol (2013)
Gross lesions, histopathology and microbiological analysis of samples from 27weaned alpaca tuis from southern Peru that died from acute pneumonia are described. In situ viral antigens [Parainfluenza 3 (PI3), bovine respiratory syncytial (BRSB) and bovine adenovirus type 3 (BAdV-3)] were searched in 15 of the 27 samples by direct immunofluorescent test and bacteriology cultures were performed on all 27 samples. The gross alterations corresponded mostly to extensive multilobar pneumonia (11/27) associated with fibrinous pleuritis (8/27), and congestion and pulmonary edema (8/27). With the exception of peribronquial lymphocitic aggregates observed in one case, the histopathological changes were similar to those described in the literature for acute pneumonia in neonatal cases. In 9 out of 15 pneumonic tissues, 14 viral antigens were detected (5 as single, 3 dual and 1 triple infections). BRSV was detected 5 times, PI3 5 times, and BAdV3 4 times, coexisting most frequently with Pasteurella multocida (n=15) and Mannheimia haemolytica (n=10). These results show that the acute pneumonia process in alpaca tuis is produced by viral and bacterial interactions, as has previously been documented for alpaca neonates and in other ruminants.